Curricular intersections of university extension and teaching in Physical Therapy programs - Shamyr Sulyvan de Castro; Ana Inês Sousa; Miriam Cristina Pontello Barbosa Lima
Introduction University extension can be a vehicle for social change and aid in the education of university students; however, it is important to study how it is inserted in university programs so that educational actions and policies can be planned more adequately. Objectives To study the insertion of extension activities in undergraduate physical therapy curricula in Brazilian federal universities. Method Documentary research conducted by accessing files available on the Internet. Data were analyzed quantitatively in the form of numbers and percentages. We examined documents from 22 of the 29 federal universities that offered physical therapy programs. Results University extension takes the form of complementary academic activities together with other options such as participating in conferences, specific training courses and working as a teaching assistant. Undergraduate physical therapy courses have a 4,000h to 4,925h course load, of which 0.72% to 8.9% are dedicated to extension activities. Conclusion The data indicate that the insertion of extension activities in undergraduate physical therapy programs offered by Brazilian federal universities needs to be reassessed according to recommended policies and guidelines.